Astrotwins : project rescue - Kelly, Mark E. (Kelly, Mark E. Astrotwins., 2016)
"Mark Kelly and his twin brother are back for more outer space adventure, this time fixing up an abandoned Apollo command module and taking off to rescue a Russian cosmonaut who is stranded in space"--